Increasing Accounting Competency and Financial Reporting in Village Crediting Institution - Primadona, Ida Ayu Lidya; Rustiarini, Ni Wayan; Putra, I Gede Cahyadi; Yuesti, Anik (Asian Journal of Community Services, 2024)
Lembaga Perkreditan Desa (LPD) are microfinance institutions in Bali that are based on local wisdom. One form of good LPD governance is reporting LPD performance transparently and consistently to indigenous communities. Intense competition between financial institutions motivates LPD managers to improve performance and develop human resource competencies continually. This service program aims to increase the accounting and financial reporting knowledge of LPD employees. This service activity uses four methods: interviews, counseling, mentoring, and evaluation. The evaluation results show increased accounting knowledge and understanding of financial reports.